Digital Twin‐Driven All‐Solid‐State Battery: Unraveling the Physical and Electrochemical Behaviors. Issue 35 (26th July 2020) - Park, Joonam; Kim, Kyu Tae; Oh, Dae Yang; Jin, Dahee; Kim, Dohwan; Jung, Yoon Seok; Lee, Yong Min
Abstract: The digital twin technique has been broadly utilized to efficiently and effectively predict the performance and problems associated with real objects via a virtual replica. However, the digitalization of twin electrochemical systems has not been achieved thus far, owing to the large amount of required calculations of numerous and complex differential equations in multiple dimensions. Nevertheless, with the help of continuous progress in hardware and software technologies, the fabrication of a digital twin‐driven electrochemical system and its effective utilization have become a possibility. Herein, a digital twin‐driven all‐solid‐state battery with a solid sulfide electrolyte is built based on a voxel‐based microstructure. Its validity is verified using experimental data, such as effective electronic/ionic conductivities and electrochemical performance, for LiNi0.70 Co0.15 Mn0.15 O2 composite electrodes employing Li6 PS5 Cl. The fundamental performance of the all‐solid‐state battery is scrutinized by analyzing simulated physical and electrochemical behaviors in terms of mass transport and interfacial electrochemical reaction kinetics. The digital twin model herein reveals valuable but experimentally inaccessible time‐ and space‐resolved information including dead particles, specific contact area, and charge distribution in the 3D domain. Thus, this new computational model is bound to rapidly improve the all‐solid‐state battery technology by saving the research resources and providing valuable insights. Abstract : A digital twin‐driven all‐solid‐state battery provides insight into physical and electrochemical behaviors. It is anticipated that this digital twin model will be widely utilized to improve the electrochemical performance of all‐solid‐state batteries in the near future.